2014
DOI: 10.3390/ijms151120948
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells: The Pursuit of Genomic Stability

Abstract: Stem cells harbor significant potential for regenerative medicine as well as basic and clinical translational research. Prior to harnessing their reparative nature for degenerative diseases, concerns regarding their genetic integrity and mutation acquisition need to be addressed. Here we review pluripotent and multipotent stem cell response to DNA damage including differences in DNA repair kinetics, specific repair pathways (homologous recombination vs. non-homologous end joining), and apoptotic sensitivity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 122 publications
1
28
0
Order By: Relevance
“…As mentioned earlier, genomic stability can be achieved by the coordination of multiple processes referred to as DDR which includes cell cycle checkpoints, DNA repair and cell death (62, 64). Recent reviews describing DDR in adult stem cells (90) including hematopoietic stem cells (91) as well as multipotent and pluripotent stem cells (92) have been reported. This review article will mainly focus on DDR signaling in embryonic and induced pluripotent stem cells.…”
Section: Dna Damage Response (Ddr) and Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, genomic stability can be achieved by the coordination of multiple processes referred to as DDR which includes cell cycle checkpoints, DNA repair and cell death (62, 64). Recent reviews describing DDR in adult stem cells (90) including hematopoietic stem cells (91) as well as multipotent and pluripotent stem cells (92) have been reported. This review article will mainly focus on DDR signaling in embryonic and induced pluripotent stem cells.…”
Section: Dna Damage Response (Ddr) and Stem Cellsmentioning
confidence: 99%
“…Studies describing DDR in pluripotent stem cells (PSCs) and either derived differentiated cells or other somatic cells provide a wide range of outcomes (Table 1). However, it is clear that ES cells and PSCs have an enhanced activity of DNA repair proteins and DNA DSB repair (92). Upon exposure to DNA damaging agents (UV, IR, H 2 O 2 , psoralen), human ESCs showed efficient DNA repair as compared to fibroblast and HeLa cells (93).…”
Section: Dna Damage Response (Ddr) and Stem Cellsmentioning
confidence: 99%
“…Compared to somatic cells, very few studies have been conducted in pluripotent cells regarding their DDR network components. Limited reports suggested that PSCs employed distinct strategies to cope with DNA damage (Wyles et al, 2014). For instance, mouse ESCs bypass the G1/S cell cycle checkpoint due to a extremely short G1 phase (van der Laan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in genomic stability and differentiation potential among reprogrammed PSCs A fundamental concern about stem cells and their differentiated derivatives is their ability to restore physiological functionality and to resist neoplastic transformation in response to endogenous genotoxic stress (Wyles et al, 2014). Variations in differentiation potential were recently observed among isogenic PSCs generated by different reprogramming approaches (Fig.…”
Section: Resultsmentioning
confidence: 99%